A Canine Model of Hemorrhagic Transformation Using Recombinant Tissue Plasminogen Activator Administration After Acute Ischemic Stroke - Jiang, Run-Hao; Zu, Qing-Quan; Xu, Xiao-Quan; Wang, Bin; Ding, Ye; Wang, Jun; Liu, Sheng; Shi, Hai-Bin (Frontiers in Neurology, 2019)
Early reperfusion of occluded arteries via recombinant tissue plasminogen activator (rtPA) administration is considered to be an effective strategy for the treatment of acute ischemic stroke. However, delayed administration of rtPA may cause severe hemorrhagic transformation (HT) and undesirable neurological outcomes. The current study aims to establish a canine HT model using rtPA administration and to investigate the potential mechanisms underlying HT. Following anesthesia, two autologous clots were injected into the middle cerebral artery (MCA) to induce ischemic stroke. To induce reperfusion, rtPA (2 mg/kg) was administrated intravenously 4.5 h after the establishment of stroke. The occurrence of HT was determined by computed tomography (CT) and by pathological assessment. Transmission electron microscopy was utilized to assess blood-brain barrier (BBB) damage. The expression of matrix metalloprotein 9 (MMP-9) was analyzed by enzyme linked immunosorbent assay (ELISA), immunofluorescence (IF), and western blot. Administration of rtPA 4.5 h after stroke induced reperfusion in 73.9% of the canines, caused evident HT, and did not improve neurological outcomes compared to canines that did not receive rtPA. There was a significant increase in expression of MMP-9 after rtPA administration, accompanied by BBB disruption. We have established a canine HT model that closely mimics human HT by using rtPA administration after the induction of middle cerebral artery occlusion (MCAO) with autologous clots. Our data suggest that a potential mechanism underlying rtPA-caused HT may be related to BBB dysfunction induced by an increase in MMP-9 expression.